Twenty years of infant education (Journal of Parents and Teachers, 2012)
The LOGSE recognized the period of infant education (0-6 years) with characteristics such as a new currículum, education focused on children and them living more complete experiences. Later on, the LOCE decides the separation of the first years (0-3), called preescolar.  Since 2008, the plan EDUCA3 establishes the creation and renovation of 0 to 3 years schools in the whole country. Infant education keeps focusing on the child, his/her interests and needs.
Keywords: childhood education; LOGSE; LOCE; LOE; education; teaching; childcare; learning